Escape from Alcatraz [videorecording] - Daley, Robert; Siegel, Donald; Malapaso Company; Siegel Film. ([S.l.] Paramount Pictures Corp. [producer], 1980)
A reenactment of the true story of three men escaped from the maximum security prison at Alcatraz. In 29 years, the impenetrable federal penitentiary, which housed AL Capone and "Birdman" Robert Stroud was only broken once by the three men. Eastwood who portrayed Frank Morris masterminded the successful escape.
Based on the book by J. Campbell Bruce.
VHS.
Edited by Ferris Webster ; Screenplay by Richard Tuggle.
Clint Eastwood, Patrick McGoohan, Roberts Blossom.
Keywords: Feature films